RF and microwave diagnostics for compact plasma traps and possible perspectives for fusion devices. (1st January 2022) - Torrisi, G.; Naselli, E.; Di Donato, L.; Mauro, G.S.; Mazzaglia, M.; Mishra, B.; Pidatella, A.; Sorbello, G.; Mascali, D.
Abstract: Plasma diagnostics is a topic having a great impact on R&D in compact ion sources as well as in large fusion reactors. Towards this aim, non-invasive microwave diagnostics approaches, such as interferometric, polarimetric and microwave imaging profilometric techniques can allow obtaining volumetric, line-integrated or even space-resolved information about plasma electron density. Special probes can be also designed and implemented in order to characterize external and/or self-generated radio-waves in the plasmas. In particular, the design, construction and operation of a K-band microwave interferometry/polarimetry setup based on the Frequency-Modulated Continuous-Wave (FMCW) method at INFN-LNS will be described: this tool provides reliable measurements of the plasma density even in the extreme unfavorable wavelength-to-plasma scale ratio in plasma-based ion sources. A "frequency sweep" and a post-processing filtering method (for interferometry and polarimetry, respectively) were used to filter out the multipath contributions or cavity induced depolarizations in the detected signals. Besides this, the use of the aforementioned RF plasma-immersed probes will also be discussed, which allow measuring local E -fields and fast temporal response in order to characterize turbulent (through kinetic instabilities, cyclotron maser emission, etc.) vs. stable plasma regimes. An analysis based on wavelet transform applied to measurements of plasma radio self-emission in B -minimum and simple mirror traps will be presented. These tools and methods have the potential to be applied to plasma machines both in compact traps and large-size reactors with a proper scaling.